2015
DOI: 10.1186/s13071-015-0791-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against Trichinella spiralis infection induced by TsNd vaccine in mice

Abstract: BackgroundWe have previously reported that Trichinella spiralis Nudix hydrolase (TsNd) bound to intestinal epithelial cells (IECs), and vaccination of mice with recombinant TsNd protein (rTsNd) produced a partial protective immunity. The aim of this study was to investigate the immune protection induced by TsNd DNA vaccine.MethodsThe full-length cDNA sequence of TsNd gene was cloned into pcDNA3.1 and used to immunize BALB/c mice by intramuscular injection. Transcription and expression of TsNd were detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Recombinant pcDNA3.1-TsNd vaccine conferred higher levels of protection against T. spiralis infection in comparison to pcDNA3.1-TsE1. Vaccination of mice with pcDNA3.1-TsNd showed 40.44% reduction in worm adults and 53.9% reduction in ML burden with the production of a mixed Th1/Th2 systemic immune response and IgA production at the mucosal level [54]. In this case, the use of pcDNA3.1/TsNd did not increase the protection previously conferred by recombinant TsNd (57.7 and 56.9% reduction in adult and ML burden, respectively) [44].…”
Section: Third-generation Vaccinesmentioning
confidence: 74%
See 1 more Smart Citation
“…Recombinant pcDNA3.1-TsNd vaccine conferred higher levels of protection against T. spiralis infection in comparison to pcDNA3.1-TsE1. Vaccination of mice with pcDNA3.1-TsNd showed 40.44% reduction in worm adults and 53.9% reduction in ML burden with the production of a mixed Th1/Th2 systemic immune response and IgA production at the mucosal level [54]. In this case, the use of pcDNA3.1/TsNd did not increase the protection previously conferred by recombinant TsNd (57.7 and 56.9% reduction in adult and ML burden, respectively) [44].…”
Section: Third-generation Vaccinesmentioning
confidence: 74%
“…The 31 kDa E/S antigen of ML (TspE1) and TsNd, an up-regulated gene in IIL compared to ML, have been cloned in pcDNA3.1 vector [53,54]. Recombinant pcDNA3.1-TsNd vaccine conferred higher levels of protection against T. spiralis infection in comparison to pcDNA3.1-TsE1.…”
Section: Third-generation Vaccinesmentioning
confidence: 99%
“…8,47,48 It was proved that the protective effect of these genes could be significantly improved by choosing proper methods, such as constituting DNA vaccine or using a prime-boost strategy. [49][50][51] As a recombinant protein candidate antigen for anti-T. spiralis vaccine, rTsserpin showed higher protective effect than many other recombinant protein antigens, such as rNudix, rTsGST and rTspSP-1.3 47,52,53 and should deserve special attention. Ts-serpin is a very promising vaccine candidate for T. spiralis infection, and we intend to try different vaccine type with corresponding delivery route to improve the protective effect of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Several recombinant protein antigens have been found to show partial protection against T. spiralis infection . It was proved that the protective effect of these genes could be significantly improved by choosing proper methods, such as constituting DNA vaccine or using a prime‐boost strategy . As a recombinant protein candidate antigen for anti‐ T. spiralis vaccine, rTs‐serpin showed higher protective effect than many other recombinant protein antigens, such as rNudix, rTsGST and rTspSP‐1.3 and should deserve special attention.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccination of mice with the T7 phage-displayed TsNd polypeptides , recombinant TsNd protein (rTsNd) (Long et al 2014) or TsNd DNA (Liu et al 2015a;Liu et al 2015b) produced a partial protection against T. spiralis infection. The results suggested that TsNd might play critical role during the invasion of IECs by T. spiralis.…”
Section: Introductionmentioning
confidence: 99%